Tracking controller design for a nonlinear model of a gantry crane based on dynamic extension and robustification - Zárate Moya, José Luis (Pontificia Universidad Católica del Perú, 2015)
Overhead cranes are widely used in industry for transportation of heavy loads and are common industrial structures used in building construction, factories, and harbors, traditionally operated by experienced crane operators. The underlyng system consists of three main components: trolley, bridge, and gantry. Basically, the system is a trolley with pendulum. In normal operation, the natural sway of crane payloads is detrimental to the safe and efficient action. Other external disturbances parameters, wind for example, also affect the controller performance. Basically, a crane system is an underactuated system. This makes the design of its controllers complicated. Usually, this is done via the crane acceleration required for motion. The most important issues in crane motion are high positioning accuracy, short transportation time, small sway angle, and high safety. The main goal of this thesis is to achieve a robust controller design procedure, based on H∞ control theory, for a nonlinear model of a 3-D gantry crane system. The approach shall be compared with classic controllers in terms of attenuating the perturbation on the payload transportation. The model describes the position of the load, as well as the time derivatives of the position. In vew of this, flatness-based feedforward control has to be devised, accompanied by the design of an optimal linear and nonlinear feedback controller. The nomnal states can be used as optimization parameters and restrictions on stability, overshoot, position regulation, and oscillation angle, being independent of the load mass and depending on the rope length. The procedure is as follows. First, a dynamic nonlinear model of the system is obtained using the Lagrange equations of motion which describe the simultaneous travelling, crossing, lifting motions and the resultant load swing of the crane. Then, the system is exactly linearised by a dynamic extension. Next the closed-loop system, based on the linear quadratic regulator scheme, is probed and compared with the H∞ robust control system for compensating modeling errors and/or internal and external perturbation. Finally, simulation results are presented showing the efficiency of the proposed controller design scheme. Results are provided to illustrate the improved performance of the nonlinear controllers over classic pole placement and linear quadratic regulator approaches, testing its fast input tracking capability, precise payload positioning and minimal sway motion.

Kräne werden in der Industrie für den Transport schwerer Lasten eingesetzt. Man findet sie im Hochbau, Fabriken und Häfen. Traditionell werden sie von erfahrenen Kranführer betrieben. Das der Arbeit zugrunde liegende Kransystem besteht aus drei Hauptkomponenten: Transporteinheit, Brücke und Gerüst. Im Regelbetrieb ist das Schwingen von Krannutzlasten einer sicheren und effizienten Nutzung abträglich. Auch andere externe Störparameter wie beispielsweise der Wind haben einen Einfluss auf die Kontrollierbarkeit eines Krans. Grundsätzlich ist ein Kransystem ein unteraktuiertes System. Deshalb verkompliziert sich im Allgemeinen der Entwurf einer Regelung, meist auf Basis der Kranbeschleunigung. Regelziele bei der Kranbewegung sind u.a. eine hohe Positioniergenauigkeit, kurze Transportzeit, kleine Pendelwinkel und hohe Sicherheit. Das Hauptziel dieser Diplomarbeit ist der Entwurf einer robusten Reglung, gründend auf der H∞-Regelungsttheorie, für ein nichtlineares Modell eines 3-D-Portalkran- Systems. Das Verfahren soll mit dem klassischen Controllerdesign verglichen und resultierende Regelungsprobleme infolge von Störungen im Nutzlasttransport untersucht werden. Das Modell beschreibt die Position der Last sowie deren zeitliche Ableitungen. Davon kann das Problem für den Entwurf einer flachheitsbasierten Vorsteuerung abgeleitet werden, die dann mit einer optimalen, linearen bzw. nichtlinearen Regelung verbunden wird. Die nominalen Zustände können als Optimierungsparameter und Beschränkungen für die Stabilität, Überschwingen, Positionsregelung und Schwingungswinkel verwendet werden, unabhängig von der Lastmaße und in Abhängigkeit von der Seillänge. Dabei wird wie folgt vorgegangen: Zunächst wird ein nichtlineares Systemmodell mit Hilfe der Lagrange-Gleichungen erstellt. Dann wird das System mit Hilfe einer dynamischen Erweiterung exakt linearisiert. Als nächstes wird der geschlossene Regelkreis auf Basis der linear-quadratischen Regelung untersucht und mit einer robusten H∞ Regelung zur Kompensation von Modellierungsfehlern oder systeminterner und -externe Störung verglichen. Schließlich werden Simulationsergebnisse vorgestellt, welche die Wirksamkeit des Entwurfes belegen. Ein Ergebnis st dabei die verbesserte Leistung des nichtlinearen Reglers gegenüber dem klassischen Regler. Dies wird anhand einer Fähigkeit zu Verfolgung einesr schnellen Bahn, der Präzision der Positionierung und der minimalen Einflussbewegung der Nutzlast dargestellt.
Keywords: Control automático; Gruas; Mecánica no lineal; https://purl.org/pe-repo/ocde/ford#2.03.01